Maqashid Syariah dan Kesejahteraan Masyarakat Lokal di Kawasan Destinasi Wisata Sungai Kapuas - Safira, Laila; Hakim, Luqman; Kalbarini, Rahmah Yulisa (Jurnal Iqtisaduna, 2024)
Tourism development is considered necessary to realize the welfare of the community, especially community, this welfare is not only seen from income alone but also Maqashid sharia. This research aims to see how the fulfillment of the needs if local communities aroud the Kapuas River tourist area seen from Maqashid Sharia. This research uses a descriptive method with a qualitative approach. The data collection techniques used were observation, interview, and documentation. Data were obtained from informants, such as Pontianak City Tourism Office, local community leaders and local communities. Based on the data collection and processing techniques above, the conclusions of this study are; The existence of the Kapuas River Tourism Area with existing tourism carrying capacity is able to improve the economy of the surrounding community. Judging from the increase in efforts to fulfill the needs of hajiyah and tahsiniyah needs. While in Maqashid sharia, this tourist area provides the potential to fulfill the needs for Hifsz al-Din (Maintenance of Religion), Hifdz al-Nafs (Maintenance of Life), Hifdz al-Aql (Maintenance of Intellect), Hifdz al-Nasl (Maintenance of Descent), Hifdz al-Mal (Maintenance of Property).